Surface Plasmon Resonance Sensor Based on Double-Sided Polished Microstructured Optical Fiber Coated With Graphene-on-Silver Layers - Donglian Hou; Nannan Luan; Xianxing Ji; Wandi Zhang; Zhiwei Zhang; Xia Jiang; Li Song; Yaoyao Qi; Jianfei Liu (IEEE Photonics Journal, 2022)
We propose a concept of surface plasmon resonance sensor based on double-sided polished microstructured optical fiber coated with graphene-on-silver layers. The silver films on the polishing planes are covered with multilayer graphene which can prevent the oxidation of silver and enhance the adsorption of biomolecules. The sensing performance of the proposed sensors with polishing planes angle of 0°, 60° and 120°, are investigated by using both wavelength and amplitude interrogations. Our numerical results demonstrate that increasing the size of the air hole in the core area can effectively improve the wavelength and maximum amplitude sensitivities. Moreover, growing number layer of graphene can increase wavelength sensitivity, whereas decrease the maximum amplitude sensitivity.